Membangun masyarakat demokratis yang bermoral lewat Pendidikan Kewarganegaraan - Sunarso, Sunarso (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
Expectation which still be remained from Indonesian nation in order to get out of various crises is by improving education system. National education is aimed at developing the competence of student to become pious and religious human which have civilized and kindness, healthy, knowledgeable, capable, creative, self-supporting, and become democratic citizen and responsible. Civic Education owns the strategic role in forming democratic and responsible citizen and building the democratic society. Hoped competences after undergoing civic education is the awning of a set smart action, full of responsibility from a citizen in relating to state, and also able to have a share in finding various problem faced by the society, nation and state as according to profession and capacities of each.